Evaluation of the effects of pesticides, used on table grapes, on the mealybug parasite, Coccidoxenoides peregrinus (Timberlake) (Hymenoptera: Encyrtidae) - Walton, Vaughn M.(Vaughn Martin) (Stellenbosch : Stellenbosch University, 2012)
Study project (M. Sc.) -- University of Stellenbosch, 1998.